Implementation of The Bansos Program as An Effort to Improve Community Welfare During The Covid-19 Pandemic in Sentul Village, Tangerang District - Bangun, Nadia Oktaviani; Suryani, Suryani; Raya, Fitri (Institut Agama Islam Sunan Giri Ponorogo, 2022)
This study aims to determine the implementation of the social assistance program and improve the Welfare of the people of Sentul Village, Tangerang Regency. The performance of distribution of social assistance is often an improvised program that is only aimed at easing and helping the people's economy during the pandemic. This impacts the limited time needed to validate household data, causing problems in collecting data on the distribution of social assistance, which leads to community dissatisfaction. This study aims to determine the implementation of the social assistance program and improve the Welfare of the people of Sentul Village, Tangerang Regency. The research method uses a descriptive qualitative approach through observation, interviews, and documentation. The results of the study show that the implementation of the social assistance program has been carried out following the data obtained by the local RT. However, this social assistance program can be said to be uneven and not well-targeted.